Peran Mahasiswa Dalam Mewujudkan UINSU sebagai Kampus yang Berkeadaban: - Dara Mukhlishah Pulungan; Irwansyah Irwansyah (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This article or writing aims to find out the role of students in realizing UIN North Sumatra as a civilized campus with case studies at the Faculty of Syari’ah and Law, State Islamic University of North Sumatra. The problems in this article are focused on students' views of UIN North Sumatra as a civilized campus and indicators that become references and the role of students in realizing UIN North Sumatra as a civilized campus. This research method uses qualitative research. Observation data collection techniques and direct interviews with interviewees with interview locations at the Faculty of Syaro’ah and Law. After the data is collected, analyze the data by using data reduction, presenting the data and concluding. The results of the study show that UIN North Sumatra is a less civilized campus. It is said so, because there are still many things that must be improved to realize UIN North Sumatra as a civilized campus. One of the things that must be applied is in terms of dressing in the campus environment which must be in accordance with Islamic law. Keywords: The Role of Students, UINSU, a Campus that Is Civilized